2014
DOI: 10.1016/j.devcel.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

DEPDC1B Coordinates De-adhesion Events and Cell-Cycle Progression at Mitosis

Abstract: SummaryCells entering mitosis become rounded, lose attachment to the substrate, and increase their cortical rigidity. Pivotal to these events is the dismantling of focal adhesions (FAs). How mitotic reshaping is linked to commitment to divide is unclear. Here, we show that DEPDC1B, a protein that accumulates in G2, coordinates de-adhesion events and cell-cycle progression at mitosis. DEPDC1B functions as an inhibitor of a RhoA-based signaling complex, which assembles on the FA-associated protein tyrosine phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
90
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 50 publications
8
90
0
Order By: Relevance
“…The ARFGAP and RHOGAP domain-containing CNT-D1 (also called ARAP2; Table 1) lacks RHOGAP activity and acts as an ARF6 GAP (99). DEP1 and DEP2 coordinate cell cycle progression and interfere with RHOA and signaling despite lacking RHOGAP activity (100). OCRL1 has been shown to interact with GTP-bound RAC1 without the stimulation of its hydrolysis (101).…”
Section: Discussionmentioning
confidence: 99%
“…The ARFGAP and RHOGAP domain-containing CNT-D1 (also called ARAP2; Table 1) lacks RHOGAP activity and acts as an ARF6 GAP (99). DEP1 and DEP2 coordinate cell cycle progression and interfere with RHOA and signaling despite lacking RHOGAP activity (100). OCRL1 has been shown to interact with GTP-bound RAC1 without the stimulation of its hydrolysis (101).…”
Section: Discussionmentioning
confidence: 99%
“…This loss of integrinbased adhesions is sufficient to cause cells in culture to adopt a nearspherical shape -the minimum energy conformation for a cell with high cortical tension (as the sphere has the least surface area for a given vol ume). At a molecular level, this rapid change in adhesion is probably triggered by activation of CDK1-cyclin B [19][20][21][22] . Although CDK1-cyclin B directly phosphorylates sev eral adhesion complex components 23 , including integ rins 24 , focal adhesion kinase and paxillin 25 Figure 1 | Cell shape changes during mitosis.…”
Section: Entry Into Mitosismentioning
confidence: 99%
“…In addition, recent study has demonstrated that the GAP domain of DEPDC1B does not have GAP activity toward RHOA [34]. Nonetheless, it has been shown that the conserved arginine residue in the GAP domain is not required for the binding of GAP domains to Rho GTPase proteins [35].…”
Section: Resultsmentioning
confidence: 99%